2021
DOI: 10.1021/acsomega.0c05493
|View full text |Cite
|
Sign up to set email alerts
|

Active and Strippable PVA/Borax/NaBO3 Hydrogel for Effective Containment and Decontamination of Chemical Warfare Agents

Abstract: Active gels present unique potential for the decontamination of chemical warfare agents (CWAs) as they strongly adhere to surfaces, thus allowing prolonged decontamination time. Herein, we present a decontamination hydrogel based on polyvinyl alcohol/borax, which contains sodium perborate (NaBO 3 ), as an in situ source of the active ingredient hydrogen peroxide. Developed as a binary formulation, this gel instantly forms and effectively sticks when sprayed on various matrices, including porous and vertically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In contrast to physically crosslinked gels which lack mechanical strength and covalently crosslinked gels which are irreversible, dynamic covalent bonds confer the strength of a covalent bond resulting in a strong gel network necessary for shape stabilization, while the dynamic nature of the bonds result in reversible deconstruction of the gel network in response to an external stimuli. Boronate ester bonds are well known to modulate strength and impart pH-and temperature responsiveness to solvent-free polymer networks 14 and hydrogels, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] but their action in the environment of inorganic PCMs remained unexplored. A PCM of choice for this work was calcium nitrate tetrahydrate (Ca(NO 3 ) 2 $4H 2 O, CNH), an inexpensive material with a heat of fusion of 153 kJ kg −1 and low viscosity of 67 mPa s at 323 K above its melting temperature of 42 C which increases its propensity for leakage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to physically crosslinked gels which lack mechanical strength and covalently crosslinked gels which are irreversible, dynamic covalent bonds confer the strength of a covalent bond resulting in a strong gel network necessary for shape stabilization, while the dynamic nature of the bonds result in reversible deconstruction of the gel network in response to an external stimuli. Boronate ester bonds are well known to modulate strength and impart pH-and temperature responsiveness to solvent-free polymer networks 14 and hydrogels, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] but their action in the environment of inorganic PCMs remained unexplored. A PCM of choice for this work was calcium nitrate tetrahydrate (Ca(NO 3 ) 2 $4H 2 O, CNH), an inexpensive material with a heat of fusion of 153 kJ kg −1 and low viscosity of 67 mPa s at 323 K above its melting temperature of 42 C which increases its propensity for leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanical property of the PVA/BNNS‐NH 2 hydrogel is a bit ordinary compared with the elastomers and hydrogels without self‐healing ability, it is great among the self‐healing hydrogels. [ 13,14,29,30 ] The hydrogel with such great mechanical property also displayed excellent self‐healing capacity owing to the reversible crosslinking network through dynamic borate bonds. As shown in Scheme , the dynamic borate bonds were disconnected after damaging, while the dynamic borate bonds were re‐established after putting together at room temperature for 10 min, exhibiting the extraordinary self‐healing capability.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11,12 ] However, the highly dynamic network of the PVA/borax hydrogel resulted in the poor mechanical property which cannot work as the load‐bearing materials in many fields largely limited the applications. [ 13,14 ] On the other hand, the excellent mechanical property and extraordinary self‐healing property are opposed. Thus, there is always a balance between mechanical properties and dynamic self‐healing.…”
Section: Introductionmentioning
confidence: 99%
“…The use of two distinct crosslinked polymer networks constitutes an efficient way to increase the stiffness and strength of hydrogels. 27,29 Hydrogel films possess multiple advantages that have a significant effect on the decontamination efficiency, including adherence to various types of surfaces (thus allowing a prolonged decontamination time 30 ), and their ability to hydrate the contaminated surface 31,32 while delivering the active ingredients and promoting the neutralization and at the same time, entrapping the harmful agents, therefore ensuring high decontamination yields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Only a limited number of studies that address the challenges associated with hydrogel-based formulations for CWA decontamination are available in the literature. Redy Keisar et al 30 developed PVA/Borax/NaBO 3 active gel films for various types of surfaces contaminated with VX, GB, and soman. Ma et al 33 and Huang et al 34 reported a Zr-MOF/ hydrogel composite powder for the hydrolysis of organophosphorus nerve agents soman and VX from textile fibers.…”
Section: ■ Introductionmentioning
confidence: 99%